Computer Science for Green Technologies and Sustainable Development: Invited session Report at KES 2023 - Zema, Tomasz (Władza Sądzenia, 2023)
This report provides an overview of the Invited Session titled "Computer Science for Green Technologies and Sustainable Development", held during the 27th International Conference on Knowledge-Based and Intelligent Information & Engineering Systems from September 6–8, 2023, in Athens, Greece. The session was co-chaired by Adam Sulich and Tomasz Zema, with additional organizational support from Letycja Sołoducho-Pelc. The session requirement was attendance by participants in person. The purpose of this report is to summarize the papers presented and the discussions that took place within the session. Therefore, this paper has a descriptive approach and does not attempt to combine the presented papers.